Bacteriocin producing lactobacilli strains as a biological strategy to control listerial growth - García, María José (2015)
Listeria monocytogenes causes listeriosis in humans and animals, and is predominantly transmitted by ingestion of contaminated food. Its severity and high mortality rate make listeriosis a relevant foodborne disease. Currently, biological strategies using probiotic lactobacilli to prevent and control infectious diseases are being globally investigated. The biocontrol exerted by certain Lactobacillus spp. is mainly due to the production of a variety of antimicrobial substances. The aims of this work were (1) to investigate the presence of Listeria spp. in raw cow milk and (2) to determine the inhibitory activity of bacteriocin-like inhibitory substances (BLIS-es) produced by Lactobacillus fermentum L23 and Lactobacillus rhamnosus L60 on L. monocytogenes and other listerial species isolated from food and clinical samples. The presence of Listeria spp. in raw milk was evaluated in 814 samples from 238 cows. The listerial prevalence in cattle was 0.84% and the isolates were identified as L. innocua (LI1) and L. welshimeri (LW1). A total of 29 listerial strains were used as indicator microorganisms to evaluate the antimicrobial activity of BLIS-es L23 and L60. Bioactive metabolites produced by these lactobacilli strains were able to inhibit the listerial growth. This biological activity was mainly attributed to the BLIS-es L23 and L60 which, even at low concentration, were active on 100% of listerial strains. This study reveals a strong potential for the biotechnological use of these bacteriocin producing lactobacilli as a biostrategy against Listeria spp.